TRANSFORMASI DIGITAL SISTEM INFORMASI PENJUALAN OBAT APOTEK QILAH SEHAT MENGGUNAKAN MODEL KESUKSESAN DELONE AND MCLEAN - Murniasih, Intan; Zulhamdani, Zulhamdani; Amat Basri (Yayasan Nusantara Hasana Berdikari, 2025)
Digital transformation in the implementation of drug sales information systems is one of the needs for pharmacies to improve operational efficiency, data accuracy, and customer satisfaction in the drug sales transaction process. This research was conducted at the Qilah Sehat Pharmacy which previously still used conventional methods, namely by recording sales data in notebooks. Causing problems such as: slow transaction processes, inaccurate stock data, difficulty in recapitulating reports, limited access to management information, and low user satisfaction levels. The purpose of this research is to implement the digital transformation of drug sales transactions in a systematic manner by applying the DeLone and McLean success model. This research was also carried out by conducting observational case studies and interviews on the research target (system users). The results of this study are in the form of the implementation of Digital SI based on Point of Sale (PoS) which is integrated with stock management, automatic reports, management dashboards, and online ordering features that are able to improve system quality (score 4.50), information quality (score 4.50), and service quality (score 4.56). In addition, the use of the system is rated high (score 4.38) and user satisfaction is in the high category. The net benefits obtained include increased transaction efficiency, reduced recording errors, improved stock data accuracy, and support strategic management decision-making. The drug sales information system at Apotek Qilah Sehat has been proven to be able to improve the operational performance of pharmacies while providing effective services for customers.